A study on: the customer service of Management System Certification Department SIRIM QAS International Sdn. Bhd. / Mohd Haziq Samsudin - Samsudin, Mohd Haziq (Faculty of Business and Management, 2010)
The issue of this report is the customer service of SIRIM QAS International Sdn. Bhd. which is based on the services given from the Management System Certification Department, Sales and Customer Service section that I have been position on my bachelor practicum on 30 November 2009 until 16 April 2010. The purpose of this study is to examine the Management System Certification Department, Sales and Customer Service section from SIRIM QAS International Sdn. Bhd. (Shah Alam) services to their customers at the counter, telephone and e-mail. The methodology to gain the data is by observing all the customer services that the Management System Certification Department, Sales and Customer Service section workforce given to its entire customers from all the segments of customer service. The observation is supported by the secondary data from the section data to complete an efficient report. The expected finding from this study is to gain knowledge on how the SIRIM QAS International Sdn. Bhd. provide customer service to its customer and also to recommended new and more effective customer service for the company to be more successful in the business.